2010
DOI: 10.7863/jum.2010.29.5.691
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Interosseous Nerve of the Elbow

Abstract: Objective. In our clinical practice, we have noted a caliber change of the posterior interosseous nerve (PIN) at the elbow as seen in the long axis on sonography simulating nerve entrapment. The objective of this study was to characterize the PIN using sonography in asymptomatic individuals. Methods. Our study retrospectively characterized the PIN in 50 elbows of 47 asymptomatic patients with sonography. Measurements of the PIN in a short‐axis cross section using the circumferential trace technique and the ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 12 publications
(17 reference statements)
0
8
0
1
Order By: Relevance
“…In 2010, the American investigators drew attention to the phenomenon of physiological change of shape of the nerve at the entry to the supinator muscle ( 52 ) . They described 50 elbows in 47 asymptomatic patients and found that despite nerve flattening at its entry to the supinator muscle, its cross-sectional area does not change in a significant way.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2010, the American investigators drew attention to the phenomenon of physiological change of shape of the nerve at the entry to the supinator muscle ( 52 ) . They described 50 elbows in 47 asymptomatic patients and found that despite nerve flattening at its entry to the supinator muscle, its cross-sectional area does not change in a significant way.…”
Section: Discussionmentioning
confidence: 99%
“…Angulation was observed in 7 patients (67.6%). To date, only Martinoli et al ., in 2004, drew attention to the relationship of the shape of the nerve and the position of the forearm in which the nerve is assessed ( 52 ) .…”
Section: Discussionmentioning
confidence: 99%
“…8,[33][34][35] Fourteen studies reported multiple means at a given anatomical site, such as separate means for males and females, or for right and left sides. 20,[34][35][36][37][38][39][40][41][42][43][44][45][46] The greatest variability in nerve CSA was seen in the brachial plexus, tibial-popliteal fossa, and all three sciatic nerve small groups. When combining all anatomical locations for individual nerve measurements, the tibial nerve (n = 2916 nerves) was the most assessed, followed by the common fibular nerve (n = 2580 nerves), radial nerve (n = 2326 nerves), sciatic nerve (n = 1470 nerves), sural nerve (n = 1316 nerves), and brachial plexus (n = 1314 nerves).…”
Section: Resultsmentioning
confidence: 99%
“…The remainder of studies did not indicate the methods utilized to determine CSA (6.4% of nerve measures), 33,34,[86][87][88][89][90][91][92] or used tracing, but did not specify the precise technique (9.4% of nerve measures). 38,40,43,45,46,[93][94][95][96] Full details regarding CSA technique and ultrasound equipment utilized are included in Appendix S1. The vast majority of studies did not use the zoom function; however, those that did are indicated with an asterisk next to the transducer frequency information in Appendix S1.…”
Section: Resultsmentioning
confidence: 99%
“…However, ultrasound is being used more frequently in various clinical settings to evaluate the injury and recovery phases of nerve, thus influencing the diagnosis and clinical care of symptomatic patients[13535455]. The sudden onset and severity of the earthquake led to peripheral nerve injuries in many unique cases, which allowed us to evaluate the natural history of these injuries and the impact of surgical treatments in the recovery of these nerves.…”
Section: Discussionmentioning
confidence: 99%